Evaluating accessibility of Malaysian public universities websites using AChecker and WAVE - Ahmi, Aidi; Mahmood, Rosli (Universiti Utara Malaysia, 2016)
Websites become essential means for most universities to communicate, exchange of relevant information and enable transactions among their stakeholders.Therefore, website accessibility accessible website is crucial to students to ensure equal access to of the university's information regardless of their physical disabilities and other possible limitations.This study reports the web accessibility of 20 Malaysian public universities based on AChecker and WAVE.The results suggest a relatively low level of compliance to the guidelines as specified in WCAG 2.0 and Section 508. Among the aspects that deserve immediate attention are the provision of text alternatives for any non-text contents, keyboard accessibility and colour contrast.Other concerns such as navigation, adaptability, input assistance, compatibility, empty link and empty heading can be further improved. Regardless of low conformance, most websites extensively integrated some of the accessibility features as set out by Section 508.Overall, this study offers meaningful insights, particularly to web developers for better compliance with the standards while designing their websites.